The Effect of Lavender Aromatherapy on Reducing Afterpain in Postpartum Mothers in Purwakarta Regency, Indonesia - Resa Reviani; Amalia, Mayta Tazkiya (Journal of Anesthesiology and Clinical Research, 2024)
Introduction: Afterpain is cramping pain that occurs in the stomach of postpartum mothers after giving birth. This pain can interfere with activities and reduce the mother's quality of life. Lavender aromatherapy has been proven effective in reducing pain in several conditions. This study aims to determine the effectiveness of lavender aromatherapy in reducing afterpain in postpartum mothers in Purwakarta Regency. Methods: This research uses a quasi-experimental design with a pre-test and post-test design. A total of 60 postpartum mothers were randomly divided into two groups: the intervention group (lavender aromatherapy) and the control group (no intervention). The intervention group was inhaled with lavender aromatherapy for 30 minutes twice a day for 3 days. The control group was not given any intervention. Afterpain was measured using the visual analogue scale (VAS) on the first, third, and seventh days postpartum. Results: The results showed that there was a significant difference in the reduction of afterpain between the intervention group and the control group on the third (p=0.002) and seventh (p=0.001) postpartum day. Conclusion: Lavender aromatherapy is effective in reducing afterpain in postpartum mothers in Purwakarta Regency.